Perbandingan Komposisi Kimia dan Uji Hedonik terhadap Perisa Menggunakan Bahan Baku Limbah Ikan yang Berbeda - Siti Nurul Hikmah; Lia Handayani; Nurhayati Nurhayati (Jurnal TILAPIA, 2023)
Abstract:  Fish skin and bones contain high calcium and phosphorus, besides that they also contain minerals, proteins, and volatile compounds (Pratama et al., 2017) so that they can be used as natural flavor enhancers, because the need for natural flavor enhancers is higher due to high awareness consumers of healthy food. Along with the development of science and technology, lifestyle changes towards a healthy life and without preservatives are increasingly resonant. Public knowledge about the dangers of consuming synthetic MSG in the long term is getting higher. So processing fish waste into flavoring is one of the most useful breakthroughs in the world of science. Making a delicious and nutritious flavoring comparable to synthetic flavoring is a challenge. This study used fish broth raw materials TT, KT, TL and maltodextrin. The addition of maltodextrin to food aims to maintain the nutritional content during processing, increase solubility and organoleptic. The purpose of this study was to study the characteristics of natural flavors made from different fish waste and to determine consumer acceptance of products made from the resulting natural flavors. The test parameters observed were proximate analysis and hedonic organoleptic tests. Nonparametric data were analyzed using the Kruskall-Wallis then the Mann-Whitney test and the Bayyes test. The results of the research were carried out using the proximate test, namely the water content in the TT broth was 10.50%, the KT broth water content was 7.99%, and the TL broth water content was 10.46%. The ash content in the TT broth was 12.85%, the ash content in the KT broth was 10.23%, and the ash content in the TL broth was 11.42%. The fat content in TT broth was 1.82%, the fat content in KT broth was 1.80%, and the fat content in TL broth was 1.39%. The protein content in the TT broth was 5.88%, the protein in the KT broth was 6.89%, the protein in the TL broth was 7.54%. Based on the best hedonic organoleptic test, namely leubim bone powder broth with the addition of maltodextrin of 2.63. The results of the hedonic test showed that almost all the parameters tested, namely color, aroma, taste, texture and appearance, had a high average organoleptic score.Keywords:Bubuk Kaldu Perisa Alami , Limbah Ikan, Maltodekstrin